(untitled)
In a menopausal lady, a reduced level of estrogen hormone leads to changes in the intraocular pressure (IOP) and retinal nerve fiber layer (RNFL) thickness in the eyes. This comparative study was carried out in the Outpatient Departments (OPD) of the Community Ophthalmology and Ophthalmology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from April 2017 to June 2019 to identify any difference in IOP and RNFL thickness in pre-menopausal and post-menopausal women aged 40-65 years. In this study, 60 pre-and post-menopausal women were included. Participants 40-50 years old with irregular menstruation were classified as group A, while those 51-65 years old with no menstruation for at least 12 months were classified as group B. More than one-fourth (26.7%) of participants had HTN in group A and 53.3% in group B. HTN was significantly associated with group B. The rise in menopausal age had a significant impact on the mean IOP and RNFL. The mean IOP in right eye (RE) was 11.80 (3.31) mm of Hg in Group A and 15.63 (3.01) mm of Hg in Group B. The mean IOP in left eye (LE) was 12.27(3.78) mm of Hg and 15.47(2.84) mm of Hg in Group A and Group B, respectively. The mean IOP of both eyes was 12.03±3.48 mmHg in Group A and 15.55±2.82 mmHg in Group B. The mean difference of IOP in RE, LE and both were statistically significant between the two groups. The mean RNFL in RE was 103.97±7.42 μm in Group A and 98.90±